Paired Storytelling Learning to Improve Students' Speaking Skill at Elementary School - Afrida Juliani; Zunidar (JIP Jurnal Ilmiah PGMI, 2025)
The purpose of this study was to: (1) Obtain How the Application of the paired storytelling learning model, (2) how the skill of students in the Control class and Experimental Class, and (3) how the effect of paired storytelling learning on students' speaking skill. The method used in this study is a quantitative method, namely a type of quasi-experimental research using a post-test group design. The subjects of this study were 13 students consisting of 7 students in the experimental class and 6 students in the fifth-year control class selected through purposive sampling. Data were collected through pretest, treatment, and posttest, then analyzed using descriptive and inferential statistics. Statistical tests that support inferential analysis are used in the form of paired sample t-tests. The results of the analysis show that (1) The application of paired storytelling for class 5 can improve speaking skill by motivating students to practice paired speaking activities so that they can motivate students' self-confidence and speaking skill (2) The speaking skill of students from the control class look stagnant with decreasing achievements because the teaching methods taught after that are stagnant again. While in the experimental class that applies the paired storytelling method, students' speaking skill have increased quite significantly, such as phrases and expressions. (3) The use of the Paired Storytelling model produces a positive effect in improving the speaking ability of 5th grade students by increasing social interaction, vocabulary, practicing speaking in a fun and enjoyable atmosphere. The test results show that there is a significant difference between the two groups, a significance value of 0.00 (p <0.05) and a determination coefficient value of 58.7%, the average value of students' speaking skill in the experimental group increased significantly compared to the control group. Therefore, the use of this model has proven effective in improving speaking skill at the initial level and can then be adjusted to learning needs.